Through-The-Coating Fabrication of Fiber Bragg Grating Relative Humidity Sensors Using Femtosecond Pulse Duration Infrared Lasers and a Phase Mask - Stephen J. Mihailov; Huimin Ding; Cyril Hnatovsky; Robert B. Walker; Ping Lu; Manny De Silva (Photonics, 2023)
Fiber Bragg grating (FBG) relative humidity (RH) sensors are fabricated in commercially available polyimide (PI)-coated optical fibers with diameters of 50 and 125 μm. Infrared (800 nm) femtosecond pulse duration laser pulses and a phase mask are used to inscribe Type-I and Type-II FBGs directly through the protective polyimide coatings of both 50 and 125 μm diameter fibers without typical fiber processing such as hydrogen loading, cryogenic storage, stripping, recoating or annealing. The devices are then evaluated for their performance as humidity sensors. At telecom wavelengths, the 50 μm diameter fiber devices with a 10 μm thick PI coating had a wavelength shift of the Bragg resonance at a constant temperature of 2.7 pm/%RH, whereas the 125 μm diameter fiber devices with a 17 μm thick PI coating had a wavelength shift of 1.8 pm/%RH. The humidity sensors in the 50 µm diameter fiber demonstrated a more rapid response time to small changes in humidity and a weaker hysteresis when compared to the 125 µm diameter fiber devices. No modification to the PI coatings was observed during fabrication. No difference in RH sensitivity was observed for Type-I devices when compared with Type-II devices with the same fiber. The applicability of this approach for fabricating distributed RH sensing arrays with hundreds of sensing elements on a single fiber is discussed.